2012
DOI: 10.1007/s11033-012-2454-6
|View full text |Cite
|
Sign up to set email alerts
|

Association between PIN1 promoter polymorphisms and risk of nasopharyngeal carcinoma

Abstract: Peptidylprolyl cis/trans isomerase, NIMA-interacting 1 (PIN1) plays an important role in cell transformation and oncogenesis. Association between PIN1 promoter polymorphisms and cancer risk was reported in several cancers. This study aimed to evaluate the association between two single nucleotide polymorphisms (SNPs, -667T>C, rs2233679 and -842G>C, rs2233678) on PIN1 promoter and risk of nasopharyngeal carcinoma (NPC). The two SNPs were genotyped using polymerase chain reaction-restriction fragment length poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 29 publications
2
19
0
Order By: Relevance
“…Findings of an Italian study showed that the -667T>C SNP over-represented the T allele in the hepatocellular carcinoma cases (17). Recently, Lu et al (21) showed that the PIN1 promoter (-667T>C) polymorphism was associated with a decreased risk of nasopharyngeal carcinoma (NPC) in Chinese populations. However, it has been indicated that the variant -667C allele was not associated with risk of cancer (16,(18)(19)(20)22).…”
Section: Discussionmentioning
confidence: 99%
“…Findings of an Italian study showed that the -667T>C SNP over-represented the T allele in the hepatocellular carcinoma cases (17). Recently, Lu et al (21) showed that the PIN1 promoter (-667T>C) polymorphism was associated with a decreased risk of nasopharyngeal carcinoma (NPC) in Chinese populations. However, it has been indicated that the variant -667C allele was not associated with risk of cancer (16,(18)(19)(20)22).…”
Section: Discussionmentioning
confidence: 99%
“…We reviewed the titles, abstracts and the full texts of all retrieved articles through defined criteria. Finally, 9 studies including a total of 5427 cancer cases and 5469 controls were selected in our meta-analysis (Segat et al, 2007;Lu et al, 2009;Zhao, 2009;Han et al, 2010;Lu et al, 2011;Naidu et al, 2011;Cao, 2012;Lu et al, 2013;You et al, 2013) (Figure 1). The characteristics of the selected studies are listed in Table 1.…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…For the -842G>C polymorphism, Han et al (2010) found that -842C variant alleles (GC+CC) were associated with decreased risk in breast cancer; Lu at al (Lu et al, 2013) found that -842CG heterozygote but not -842CC homozygote had a significantly decreased risk of nasopharyngeal carcinoma; In another two studies, -842G>C polymorphism had no influence on breast cancer (Naidu et al, 2011) and hepatocellular carcinoma risk (Segat et al, 2007). For -667C>T polymorphism, some studies found that -667T allele was associated with increased risk of nasopharyngeal carcinoma (Lu et al, 2013) and hepatocellular carcinoma (Segat et al, 2007), but others found that this polymorphism had no association with esophageal carcinoma (You et al, 2013), lung cancer , breast cancer (Han et al, 2010;Naidu et al, 2011) and squamous cell carcinoma of the head and neck (Lu et al, 2009). Therefore, it is highly necessary to perform a quantitative and systematic investigation with rigorous methods.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have revealed the relationship between the PIN1 gene polymorphisms, rs2233678, rs2233679, and rs2233682, and the susceptibility of cancers, such as esophageal carcinoma, nasopharyngeal carcinoma, lung cancer, breast cancer, and squamous cell carcinoma of the head and neck (SCCHN), in various races [22][23][24][25][26]. However, to date, only one study has investigated the influence that PIN1 gene polymorphisms have on the risk of HCC [27].…”
Section: Introductionmentioning
confidence: 99%